SPEECH ACT OF SUSI PUDJIASTUTI IN FORMING PERSONAL BRANDING - Azzahrah, Nurannisa; Mustikawati, Yunitari (Faculty of Languages and Literature, Universitas Negeri Makassar, 2021)
The aim of this research is to determine the types and the functions of Speech Act by Susi Pudjiastuti in forming personal branding in public. This study uses a descriptive method based on the Searle’s theory on Illocutionary speech act. The data is taken from Pudjiastuti Speeches on Understanding Indonesia’s Marine Police: Economic and Security Challenges (2015) and World should unite agains illegal fishing (2018). The result of this research indicate that all the types ofillocutionary act. They are Representatives, Directives, Commissives, Expressives, and Declarations. The functions of speech act used by Susi Pudjiastuti are Representatives functions such as statements of fact, assertions, conclusions, and descriptions. Directive acts, namely commands, orders, requests, ask, and suggestions. Commissive function to do something to some future with uses action, they are promising, threatening, offering, refusing, and pledging. Expressive function such as thanking, congratulating, pardoning, blambing, praising, and condoling and the last is Declaratives functions such as resigning, dismissing, christening, naming, appointing, excommunicating, sentencing. By explaining the speech acts used Pudjiastuti in forming personal branding, it can be concluded that speech actsare very important in forming personal branding, both formally and informally.